1976
DOI: 10.1128/jb.128.1.337-346.1976
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a glycerol auxotroph of Rhodopseudomonas capsulata: effect of lipid synthesis on the synthesis of photosynthetic pigments

Abstract: A glycerol auxotroph was isolated from Rhodopseudomonas capsulata for use as a system for studying membrane synthesis and function. When the mutant was deprived of glycerol, net phospholipid synthesis ceased immediately and a small amount of free fatty acids accumulated. A turnover of lipid occurred in both deprived and supplemented cultures. Deoxyribonucleic acid and protein synthesis continued for one doubling of cell mass and then slowed down in deprived cells. Net ribonucleic acid synthesis slowed down mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Previous studies (5,23) employing the nonsulfur purple photosynthetic bacteria have included the use of cerulenin to inhibit phospholipid synthesis; however, these studies provided no evidence concerning the specificity of the observed inhibition. In this regard, the present study shows that exogenously supplied fatty acids are able to relieve a growth inhibition of R. sphaeroides caused by cerulenin, but the ameliorative effect of the fatty acids is conditional.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (5,23) employing the nonsulfur purple photosynthetic bacteria have included the use of cerulenin to inhibit phospholipid synthesis; however, these studies provided no evidence concerning the specificity of the observed inhibition. In this regard, the present study shows that exogenously supplied fatty acids are able to relieve a growth inhibition of R. sphaeroides caused by cerulenin, but the ameliorative effect of the fatty acids is conditional.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to the study of membrane assembly involves uncoupling protein and phos-pholipid syntheses. This has been accomplished in bacterial systems by depriving glycerol-requiring auxotrophs of this polyol (2,28,35,37,47). Under such circumstances, phospholipid is no longer synthesized, and it is possible to study the incorporation of membrane proteins independent of concomitant phospholipid insertion (34,36,37).…”
Section: Synthesesmentioning
confidence: 99%
“…Under such circumstances, phospholipid is no longer synthesized, and it is possible to study the incorporation of membrane proteins independent of concomitant phospholipid insertion (34,36,37). During cessation of phospholipid synthesis in a glycerol auxotroph of the related photosynthetic bacterium Rhodopseudomonas capsulata, protein synthesis continued for one doubling, whereas that of bacteriochlorophyll a (Behl) and carotenoids was markedly inhibited (28). An association between the synthesis of phospholipid and photosynthetic pigments was demonstrated previously during chromatophore membrane induction in R. sphaeroides (30).…”
Section: Synthesesmentioning
confidence: 99%
“…The events that follow appear to be directly or indirectly caused by the lack of ongoing phospholipid synthesis and not by any consequent abnormality in the composition of the phospholipids. In general, phospholipid turnover in this organism is very slow, approximately 10% per generation (6), compared to approximately 40% in Escherichia coli (31) and 60% in Rhodopseudomonas capsulata (23).…”
Section: Discussionmentioning
confidence: 99%